RESEARCH PROJECTS TO STUDY THE SEA FLOOR AND SUB-BOTTOM SEDIMENTS FUNDED BY THE RECENT EUROPEAN COMMISSION FRAMEWORK PROGRAMS: THE I.G.M.E. PARTICIPATION - Perissoratis, C.; Ioakim, Chr. (Bulletin of the Geological Society of Greece, 2010)
Since 1983, after the participation of Greece in the European Union (EU), IGME has carried out many research projects relevant to earth sciences funded by the European Commission (EC). Especially in the sector of Marine Sciences, a number of projects have been funded in cooperation with other European Institutes. The main targets of the research projects were relevant to the tasks described in the various framework programs (FP) evaluated by the EC, with the tasks changing according to the decision of the European Parliament. The marine projects became gradually larger in terms of the number of the participating Institutes while their target focused more toward to the society needs such as the sustainable energy resources and environmental problems. In this presentation we will describe the research projects relevant to the above targets that were carried out in the last 10 years partly or entirely in the Greek seas.